Risk Factors for Flares and New Lesions of Hidradenitis Suppurativa Following COVID-19 Disease: A Retrospective Cohort Study of 310 Patients in Greece - Aikaterini I. Liakou; Andreas G. Tsantes; Evangelia-Konstantina Bompou; Magdalini Kalamata; Efthymia Agiasofitou; Soultana Vladeni; Angeliki Dragoutsou; Konstantina A. Tsante; Petros Ioannou; Eleni Chatzidimitriou; Ourania Kotsafti; George Samonis; et al. (Microorganisms)
Background: COVID-19 disease has been associated with flares or new onsets of various autoinflammatory diseases such as psoriasis and atopic dermatitis. Our aim is to investigate the occurrence and risk factors of flares or new onsets of Hidradenitis Suppurativa (HS) following COVID-19 disease. Methods: A retrospective cohort study was performed including 310 patients with HS following COVID-19 disease. Data on the rate of HS flares, new lesions, time of flare onset, and flare duration were recorded. Demographics, clinical characteristics, and treatment parameters were compared between patients with and without HS flares. Results: HS flares developed in 69 (22.2%) patients, with 14 experiencing their first episode. The median period between COVID-19 and flare onset was 17 days, with a median flare duration of 14 days. For new HS onset, the median period was 9.5 days, and the median duration was 13 days. Biologic treatment was less common in patients with flares (7.2% vs. 23.2%, p = 0.003), and fewer patients with flares were vaccinated (81.1% vs. 99.1%, p < 0.001). Multivariable analysis showed lower risk for flares in those receiving biologics (aOR = 0.14, p = 0.002) and those who were vaccinated (aOR = 0.02, p < 0.001). Conclusions: COVID-19 may trigger HS flares and new onset, with biologic treatment and vaccination offering protection.